2020
DOI: 10.1108/jepp-08-2019-0065
|View full text |Cite
|
Sign up to set email alerts
|

Does occupational licensing costs disproportionately affect the self-employed?

Abstract: PurposeThe purpose of this study is to analyze how occupational licensing costs within a state affect the performance of self-employed firms, as measured through annual sales.Design/methodology/approachThis study utilizes an empirical approach to determine if there are additional effects on the annual sales for firms that are self-employed in high-cost states that are not explained through the individual estimations. Since the choice of self-employment is plausibly nonrandom, this study also uses a propensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Despite government attempts to attract business through incentive schemes or even to prevent bad business practices from altering the marketplace, empirical evidence suggests that facilitating business development through incentives does little and, in the case of regulation, it can actually hurt (De Soto, 2002; Klapper et al. , 2006; Minniti, 2006; Kreft and Sobel, 2005; Bruce and Mohsin, 2006; Plemmons, 2020; Johnson and Kleiner, 2020). Indeed, many studies [4] have shown negative business entry rates associated with government business regulation generally, and several eminent cross-country studies that have evaluated the impact of entry-specific regulation on firm development have found similar relationships.…”
Section: Literature On Business Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite government attempts to attract business through incentive schemes or even to prevent bad business practices from altering the marketplace, empirical evidence suggests that facilitating business development through incentives does little and, in the case of regulation, it can actually hurt (De Soto, 2002; Klapper et al. , 2006; Minniti, 2006; Kreft and Sobel, 2005; Bruce and Mohsin, 2006; Plemmons, 2020; Johnson and Kleiner, 2020). Indeed, many studies [4] have shown negative business entry rates associated with government business regulation generally, and several eminent cross-country studies that have evaluated the impact of entry-specific regulation on firm development have found similar relationships.…”
Section: Literature On Business Developmentmentioning
confidence: 99%
“…See, for example, Kleiner (2000), Kleiner and Krueger (2013), Kleiner (2006), Kleiner et al. (2016), Plemmons (2020), Timmons (2021), Thornton et al. (2017), Timmons et al.…”
Section: Notesmentioning
confidence: 99%
See 3 more Smart Citations